(untitled) (Nigerian Journal of Pharmaceutical Research, 2025)
Background: Modification of some crude extracts have improved the stability, functional properties and process ability of their bioactive. Objective: To fabricate bioactive from Securidica longipedunculata root bark and compare its activities with the crude extract. Methods: Modified extract was fabricated from Securidica longipedunculata root bark using microencapsulation and freeze drying technique, and evaluated. Results: Fourier Transform Infrared Spectroscopy evaluation showed similar leading peaks in the crude and fabricated extracts, indicating absence of chemical alteration from modification. Energy-Dispersive X-ray (EDX) of the fabricated extract revealed no new detectable element from the EDX of the crude extract, indicating chemical similarities in the crude and fabricated extracts. Scanning Electron Microscopy (SEM) of crude extract revealed flatbed surface with no observed particles, while SEM of fabricated extract revealed distinct, larger and sharp edged particles, indicating structural changes from modification. In comparison to crude extract, fabricated extract showed controlled dissolution, starting with lower dissolution over 30 min, on to higher dissolution after 45 min. At 20 – 100 mcg / ml actives, Vitamin E showed 60 – 80 % lipid peroxidation, while crude and fabricated extracts both showed 12 – 20 % lipid peroxidation, indicating that modification did not significantly alter the antioxidant efficacy of Securidaca longipedunculata crude extract material. Conclusion: The physicochemical and biological properties of fabricated Securidaca longipedunculata root bark extract showed promise in fast delivery of bioactive. There is need for further in vivo studies to ascertain the therapeutic potential of this fabricated form.